2013
DOI: 10.3109/02688697.2012.757293
|View full text |Cite
|
Sign up to set email alerts
|

Role of simvastatin in prevention of vasospasm and improving functional outcome after aneurysmal sub-arachnoid hemorrhage: a prospective, randomized, double-blind, placebo-controlled pilot trial

Abstract: There was benefit of simvastatin in terms of reduction in clinical vasospasm, mortality or improved functional outcome, however, this was not statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(93 citation statements)
references
References 18 publications
0
92
1
Order By: Relevance
“…Simvastatin has a beneficial therapeutic effect on reducing cognitive dysfunction after aSAH (16). Clinical trials have demonstrated that simvastatin reduces CVS and mortality and improves functional outcomes, although these findings were not statistically significant (4). Patients who are treated with statins prior to aSAH tend to have a lower incidence of subsequent CVS (17).…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Simvastatin has a beneficial therapeutic effect on reducing cognitive dysfunction after aSAH (16). Clinical trials have demonstrated that simvastatin reduces CVS and mortality and improves functional outcomes, although these findings were not statistically significant (4). Patients who are treated with statins prior to aSAH tend to have a lower incidence of subsequent CVS (17).…”
Section: Introductionmentioning
confidence: 71%
“…Of these 17 studies included in the meta-analysis, 5 were concerned with the biological effects of statins, 5 were controlled trials that enrolled 930 patients to study clinical efficacy, and 7 were RCTs that enrolled 347 patients and that met the inclusion criteria (2,4,7,13,14,23,25).…”
Section: Zhang Bf Et Al: Statins For Aneurysmal Subarachnoid Hemorrhagementioning
confidence: 99%
See 1 more Smart Citation
“…Other accepted therapeutic options include calcium channel blockers, endothelin receptor antagonists, sympatholytics, and intra-arterial papaverine. In addition, there are a number of less accepted but theoretically useful methods to prevent vasospasm, which include magnesium, statins, and nitrates [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, a randomized, double-blind, placebo-controlled pilot study of simvastatin and a systematic review revealed no significantly beneficial effect of statins in patients with aSAH [40]. In 2013 another trial showed that simvastatin had benefit in reduction of clinical vasospasm and mortality as well as improvement of functional outcomes, but it was not statistically significant [41]. A systematic review and meta-analysis for patients with SAH shows no benefits of statins-use to reduce the incidence of vasospasm, which was quite different from the results of previous meta-analysis [42].…”
Section: Statinsmentioning
confidence: 99%